Algeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper discusses measures needed to improve public spending efficiency to foster more inclusive growth in Algeria. Fostering more inclusive growth in a sustainable way requires addressing Algeria's longstanding structural issues that have led to persistently high unemployment, weak private sector job creation, and insufficient quality of public services. To help reverse this situation, particularly in an environment of dwindling financial resources, Algeria should improve the efficiency of public spending, including through strengthening public wage bill and investment management. This would enable the country to increase the return on investment in human capital and infrastructure, and improve the quality and reach of public service delivery. It would help ensure that the public sector fosters private sector activity rather than competes with it.